Left inferior frontal cortex can compensate the inhibitory functions of right inferior frontal cortex and pre‐supplementary motor area. Issue 3 (29th August 2018) - Gavazzi, Gioele; Lenge, Matteo; Bartolini, Emanuele; Bianchi, Andrea; Agovi, Herdis; Mugnai, Francesca; Guerrini, Renzo; Giordano, Flavio; Viggiano, Maria Pia; Mascalchi, Mario
Abstract : Right‐IFG and pre‐SMA are associated with inhibitory responses. We used functional Magnetic Resonance Imaging to explore whether the contralateral homotopic regions can functionally replace them. An adolescent, with an extensive traumatic lesion of the right cerebral hemisphere having occurred 5 years earlier, performed a motor response inhibition task (Go/Nogo), which was properly accomplished and associated to activations in the left‐IFC, precuneus and occipital cortex. Such functional remodelling is in line with the theory of 'near equipotentiality' of the cerebral hemispheres.